Pré-hidrólise ácida de bagaço de cana-de-açúcar e sua caracterização físico-química - Morais, Alaíne Patrícia da Silva [UNESP]; Broetto, Fernando [UNESP] (EIA Energy in Agriculture, 2012)
The biomass resulting from processing sugarcane bagasse has been considered a source of cellulose with the potential production of bio-fuels. This lignocellulose can be processed into ethanol since is hydrolyzed by chemical processes (acids) or biotechnology (enzymes) which generate sugars suit for fermentation. This study had the objective to utilize physical and chemical pre-treatment processes for prehydrolysis of sugarcane bagasse. The experimental treatment was adjusted at a factor of 4 X 2, by the combination of pre-hydrolysis timing (15, 30, 45 and 60 minutes) and sulfuric acid concentrations (7.0% and 9.0%) which was incubated at a temperature of 121° C in an autoclave. The treatment data was subjected to analysis of the variance and averages which were compared using the Tukey test with a probability of 5%. The results obtained showed that through pretreatment acid applied on the lignocellulose material, there was a significant break from the substrate fibers like cellulose, hemicellulose and lignin.

A biomassa resultante do processamento da cana-de-açúcar como o bagaço, tem sido considerada como fonte de celulose com potencial para a produção de biocombustíveis. Este material lignoceluló- sico pode ser transformado em etanol desde que sua estrutura seja hidrolisada por processos químicos (ácidos) ou biotecnológicos (enzimas) gerando açúcares fermentescíveis. Este trabalho teve como objetivo a utilização de processos de pré-tratamento físico e químico para a pré-hidrólise do bagaço de cana-deaçúcar. Para o delineamento experimental foi utilizado tratamento ajustado em fatorial 4 X 2, pela combinação do tempo de pré-hidrólise (15, 30, 45 e 60 minutos) e concentração do ácido sulfúrico (7,0 e 9,0 %) sendo que a incubação foi à temperatura de 121°C em autoclave. Os dados foram submetidos à análise de variância e as médias dos tratamentos foram comparadas pelo teste de Tukey, a 5% de probabilidade. Os resultados obtidos mostraram que através do pré-tratamento ácido aplicado no material lignocelulósico houve quebra significativa das fibras do substrato, como celulose, hemicelulose e lignina.
Pre-acid hydrolysis of sugarcane bagasse and its physicochemical characteristics
Keywords: Biomass; Acid treatment; Cellulose; Biomassa; Tratamento ácido; Celulose